DETERMINAN KUALITAS LABA - Alfiani Putri; Hayuningtyas Pramesti Dewi (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
The purpose of this study is to investigate factors that may influence earnings quality, namely the Investment Opportunity Set, the Independent Board of Commissioners, and the Audit Committee. Data were obtained from the Indonesia Stock Exchange, specifically the annual reports of Heavy Construction, Civil Engineering, and Telecommunication companies, and were tested using multiple linear regression analysis. The results indicate that the Investment Opportunity Set has a positive effect on earnings quality, while the Independent Board of Commissioners and the Audit Committee have no effect on earnings quality